Effect of microRNA-21 on the proliferation of human degenerated nucleus pulposus by targeting programmed cell death 4 - Chen,B. (2016)
This study aims to explore the effect of microRNA-21 (miR-21) on the proliferation of human degenerated nucleus pulposus (NP) by targeting programmed cell death 4 (PDCD4) tumor suppressor. NP tissues were collected from 20 intervertebral disc degeneration (IDD) patients, and from 5 patients with traumatic spine fracture. MiR-21 expressions were tested. NP cells from IDD patients were collected and divided into blank control group, negative control group (transfected with miR-21 negative sequences), miR-21 inhibitor group (transfected with miR-21 inhibitors), miR-21 mimics group (transfected with miR-21 mimics) and PDCD4 siRNA group (transfected with PDCD4 siRNAs). Cell growth was estimated by Cell Counting Kit-8; PDCD4, MMP-2,MMP-9 mRNA expressions were evaluated by qRT-PCR; PDCD4, c-Jun and p-c-Jun expressions were tested using western blot. In IDD patients, the expressions of miR-21 and PDCD4 mRNA were respectively elevated and decreased (both P<0.05). The miR-21 expressions were positively correlated with Pfirrmann grades, but negatively correlated with PDCD4 mRNA (both P<0.001). In miR-21 inhibitor group, cell growth, MMP-2 and MMP-9 mRNA expressions, and p-c-Jun protein expressions were significantly lower, while PDCD4 mRNA and protein expressions were higher than the other groups (all P<0.05). These expressions in the PDCD4 siRNA and miR-21 mimics groups was inverted compared to that in the miR-21 inhibitor group (all P<0.05). MiR-21 could promote the proliferation of human degenerated NP cells by targeting PDCD4, increasing phosphorylation of c-Jun protein, and activating AP-1-dependent transcription of MMPs, indicating that miR-21 may be a crucial biomarker in the pathogenesis of IDD.